2021
DOI: 10.1007/s12035-021-02353-6
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid Extract Derived from Euglena gracilis Overcomes Lipopolysaccharide-Induced Neuroinflammation in Microglia: Role of NF-κB and Nrf2 Signaling Pathways

Abstract: Activation of microglia results in the increased production and release of a series of inflammatory and neurotoxic mediators, which play essential roles in structural and functional neuronal damage and in the development and progression of a number of neurodegenerative diseases. The microalga Euglena gracilis (Euglena), rich in vitamins, minerals, and other nutrients, has gained increasing attention due to its antimicrobial, anti-viral, antitumor, and anti-inflammatory activities. In particular, anti-inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 80 publications
1
18
0
Order By: Relevance
“…We recently showed very similar results obtained with the use of an acetone extract from the microalga Euglena gracilis on the same in vitro model of neuroinflammation, despite some differences in the composition of the two extracts. Euglena gracilis extract contained diadinoxanthin as the most abundant xanthophyll, followed by zeaxanthin, whereas β-carotene represented only 8% ( Piovan et al, 2021 ). Conversely, the most abundant carotenoid present in the Spirulina extract was β-carotene, whereas the amount of zeaxanthin resulted comparable in the two extracts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently showed very similar results obtained with the use of an acetone extract from the microalga Euglena gracilis on the same in vitro model of neuroinflammation, despite some differences in the composition of the two extracts. Euglena gracilis extract contained diadinoxanthin as the most abundant xanthophyll, followed by zeaxanthin, whereas β-carotene represented only 8% ( Piovan et al, 2021 ). Conversely, the most abundant carotenoid present in the Spirulina extract was β-carotene, whereas the amount of zeaxanthin resulted comparable in the two extracts.…”
Section: Discussionmentioning
confidence: 99%
“…However, more studies are necessary to verify a possible direct interaction of the extract components with Nrf2, as already showed for some carotenoids and their derivatives that can interact with Keap1, the negative regulator of Nrf2, by changing its physical properties ( Kaulmann and Bohn, 2014 ). However, in this regard, it should be noted that, despite Nrf2 is considered a key regulator of inflammatory processes ( Ahmed et al, 2017 ), based on the existence of a complex interaction between oxidative stress and inflammation, we recently showed that the anti-inflammatory effect of the acetone extract of Euglena gracilis is Nrf2 independent ( Piovan et al, 2021 ). Similarly, the anti-inflammatory effect of E1 could be independent of the activation of Nrf2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our protocol, we used acetone as the solvent to obtain the crude extract. Indeed, we recently reported that acetone extract of Euglena is endowed with biological activity and modulated microglial activation by inhibiting the expression and release of pro-inflammatory molecules in LPS-induced neuroinflammation [38]. Moreover, acetone extracts photosynthetic pigments with a wide range of polarity and yields fractions enriched in carotenoids [39].…”
Section: Discussionmentioning
confidence: 99%
“…The sulforhodamine B (SRB) assay was used to measure microglial cell viability [75,76]. Cells were plated in poly-L-lysine coated 96-well plates (50,000 cells/well) in growth medium containing 10% of serum and allowed to adhere overnight.…”
Section: Cell Viabilitymentioning
confidence: 99%